HUBUNGAN KOORDINASI MATA-KAKI DENGAN KETERAMPILAN SEPAK SILA PADA TIM SEPAKTAKRAW SMA NEGERI PLUS PROVINSI RIAU - Juita, Ardiah Juita Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problemin this research is whether there is a relationship of eyefootcoordination with skill sila kick. The goal is to find out how big the eye-footcoordination with ability sila kick whether singly or jointly. The technique of samplingperformed with total sampling of 12 athlete of Senior High School Plus Province Riau.This research using a correlation technique. Then, the data are tested using the test ofnormality, test the product moment correlation test, test of significance on the level ofsignificance of α = 0.05. Test of normality of variabels X, L0maks (0,088) < Ltabel (0,242),and testing normality of variabels Y, L0maks (0,112) < Ltabel (0,242) in other words at aconfidence level of 95% of normal data and concluded the results showed: there is asignificant relationship between eye and food coordination with skill sila kick, withcorrelation r= 0.782, where rhitung > rtabel or 0,782 > 0,602. and such relations arecategorized strong . Thus, Ho rejected and Ha accepted.Key word: relationship, eye-foot coordination, skill sila kick.